MOTIF HIAS PADA TIANG PENYANGGAH KERATON YOGYAKARTA : TINJAUAN SEMIOTIKA DAN SOSIOLOGI SENI - Yayan H Hariansyah (UNIVERSITAS INDO GLOBAL MANDIRI, 2017)
Kraton Yogyakarta as a cultural center in Yogyakarta Special Province. has many interesting things to observe and researched one art in the field of fine arts or ornamental motifs, decorative motifs are made not just to decorate the empty space of a field but has its own meaning and philosophy, let alone decorative motifs are located on the pole buffer Kraton Yogyakarta and special places that have a sacred value. Kraton Yogyakarta has a valuable cultural value that is interesting to be studied, in this study focused on the carvings that are in the pole buffer Kraton Yogyakarta, namely Alif Motifs, Lam, Meme and Motif Ornamental Princess Merong. This decorative motif tells about the transition of the entry of Islam as the ideology of the Sultan's Palace and the rejection of the previous religion. Ornamental motifs Alif, Lam, Mim and Princess Merong will be studied with theoretical approach of signs or Semiotics, in addition to more precise and depth will be used Historical and Sociological approach of art. With the hope of this study can understand the history of the establishment and the official religion as the Sultan's Palace ideology, and can understand the textual ornament motif. Keywords : Ornamental Motif, Alif Lam Meme, Princess Merong, Kraton Yogyakarta.